Catechol-O-methyltransferase polymorphism is associated with the cortico-cerebellar functional connectivity of executive function in children with attention-deficit/hyperactivity disorder - Yoshifumi Mizuno (Nature Portfolio, 2017)
Abstract The cerebellum, although traditionally considered a motor structure, has been increasingly recognized to play a role in regulating executive function, the dysfunction of which is a factor in attention-deficit/hyperactivity disorder (ADHD). Additionally, catechol-O-methyltransferase (COMT) polymorphism has been reported to be associated with executive function. We examined whether the cortico-cerebellar executive function network is altered in children with ADHD and whether COMT polymorphism is associated with the altered network. Thirty-one children with ADHD and thirty age- and IQ-matched typically developing (TD) controls underwent resting-state functional MRI, and functional connectivity of executive function-related Crus I/II in the cerebellum was analysed. COMT Val158Met genotype data were also obtained from children with ADHD. Relative to TD controls, children with ADHD showed significantly lower functional connectivity of the right Crus I/II with the left dorsolateral prefrontal cortex. Additionally, the functional connectivity of children with ADHD was modulated by COMT polymorphism, with Met-carriers exhibiting significantly lower functional connectivity than the Val/Val genotype. These results suggest the existence of variations, such as ethnic differences, in COMT genetic effects on the cortico-cerebellar executive function network. These variations contribute to heterogeneity in ADHD. Further neuroimaging genetics study might lead to the development of fundamental therapies that target ADHD pathophysiology.